A study to indicate the effective areas that contribute to Petronas’s Corporate Social Responsibility (CSR) / Nur Syazana Abdul Hamid - Abdul Hamid, Nur Syazana (Faculty of Business and Management, 2009)
PETRONAS, the acronym for Petroliam Nasional Berhad, was incorporated on 17 August 1974 under the Companies Act 1965. It is wholly owned by the Malaysian government and is vested with the entire ownership and control of the petroleum resources in Malaysia through the Petroleum Development Act 1974. Over the years, PETRONAS has grown to become a fully integrated oil and gas corporation. PETRONAS has four subsidiaries listed on the Malaysian stock exchange Bursa Malaysia and has ventured into more than 30 countries worldwide in its aspiration to become a leading oil and gas multinational of choice. Purpose: To underlie the several area Petronas as a multinational company focused on in implying their corporate social responsibility (CSR). The research is important because CSR has become a practices of numerous of companies around the world. It also highlight the importance of having a strong brand equity that help maintain the company reputation as well as allowing themselves to compete with other oil and gas company national and internationally. Methodology: The researcher used exploratory research in order to conduct the research on the issue. In this research, 123 copies of questionnaire were distributed to the employees by using the non-probability sampling which is the convenience sampling technique. Luckily, for this study the researcher are able to collect back all the questionnaires. Means that here, the researcher get 100% feedback from the employees at Petroleum Engineering Division in PETRONAS Carigali Sdn Bhd